Locating Geodiversity Hotspots through Grid-Based Spatial Indexing: Lombok Island, Indonesia - Gathot Harbowo, Danni; Siringoringo, Luhut Pardamean (UIR PRESS, 2025)
Locating geodiversity hotspots across large areas poses a challenge for further geopark development in Indonesia, especially on Lombok Island, which spans 5,435 km². A geodiversity hotspot is an area rich in unique geological features that need to be determined. Therefore, this study's objective is to track and assess the potential of geodiversity on Lombok Island. The methods employed a grid-based spatial indexing method to pinpoint potential geodiversity hotspots in Lombok. The entire island was covered using 238 grids of 5×5 km² for this study. The technique applied these equal weight parameters: relative drainage density (20%), diversity of topographical slope (20%), elevation (20%), diversity of geological formation (20%), and soil characteristics (20%). The identified geodiversity hotspots were validated through ground checking. The results show significant geodiversity hotspots: Gangga (116°12'13.122